Effect of Heaving Movement on Flow Instability in U-Tubes of Marine Steam Generator under Natural Circulation - Jianli Hao; Wenzhen Chen; De Zhang (Science and Technology of Nuclear Installations)
Under heaving movement conditions, the single phase flow instability in U-tubes is affected by the additional force, which will influence the marine reactor operation. In the present work, one-dimensional thermal-hydraulic model in U-tubes under heaving movement conditions is established, and the critical pressure drop (CPD) and critical mass flow rate (CMFR) which relate to the occurrence of reverse flow in U-tubes are proposed and analyzed. The effects of the heaving period and heaving acceleration amplitude on the flow instability in U-tubes with the different length are discussed. It is shown that (1) the CPD and CMFR are obviously affected by the heaving movement, which means that the reverse flow characteristic in U-tubes will be changed; (2) the fluctuation periods of the CPD and CMFR are the same as the heaving period, but the fluctuation magnitude of them is little affected by the heaving period; (3) the relative changes of CPD and CMFR are the linear function of heaving acceleration amplitude; and (4) the U-tube length has little influence on the relative changes of CPD and CMFR compared with the heaving acceleration amplitude, which means that the heaving movement has little influence on the space distribution of reverse flow in the U-tubes of marine steam generator.